ADOLESCENT SELF PRESENTATION IN CYBERSPACE - Liyuts Bitul Adliyah Tsalitsy; Wiwik Juwarini Prihastiwi (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study aims to identify the differences in self presentation between female and male adolescents in the online world. This research employs a quantitative approach with 109 respondents from Surabaya, aged 11 to 21 years, from various educational backgrounds. The instrument used in this study is a self presentation scale designed based on various aspects of the variables being investigated. The data analysis technique used is statistical analysis, specifically manova, using the JASP (Jeffrey's Amazing Statistics Program) software. The results indicate significant differences in the aspects of Ingratiation (t = 1.902, p < 0.05) and Self Promotion (t = 2.381, p < 0.05), with females engaging in both behaviors more frequently than males. However, no significant difference was found in the aspect of Supplication (t = 0.233, p > 0.05) between males and females.